Peningkatkan Kreatifitas Membangun Usaha Kreatif (Simulasi Membuat Produk Sabun Cuci Piring) di Desa Domo Kecamatan Kampar Kiri Kabupaten Kampar - hadiyati, hadiyati; nofrizal, nofrizal; FATKHURAHMAN, FATKHURAHMAN (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Abstract: Purpose in this activity to achieve is for increasing knowledge about creative entrepreneur which miner simulation and practical how was process creating product plate wash. Method for this training is lecture method, practical and answer and asking and than evaluating result of training success or not with giving questioner pre-test & Post- test and the indicator success or not this event as like that with participant absent a number of 75 % from invitation has been spread and for indicator successfully level of participant understood on this program is 80 % from materialistic knowledge after done evaluate with using pre test and post test. Result after this program Ipteks for society (IbM) showed this program very utility for increasing creativity of mother of PKK in Domo village Subdistrict At Kampar Kiri, Kampar Regency. In case can look at from indicator-indicator achievement. There is level of indicator achievement from arrival participant which weather target around 80 % from 75 %. Meanwhile indicator level of participant understanding to this program also weather from target before is 85 % from 80 %. Keywords: Creativity, Entrepreneu